Reversibilitas kalsifikasi tulang akibat kekurangan protein pre dan post natal (Reversibility of bone calcification on pre and post natal protein deficiency) - Pinandi Sri Pudyani (Dental Journal (Majalah Kedokteran Gigi), 2005)
The growth and development play an important role in orthodontics mainly in bone, because it can determine the maturity of the bone. Bone maturity evaluation is very important in orthodontic treatment, because there are many individual variations in growth and development such as time, duration and velocity of the growth. Nutritional status during pregnancy and infant period will influence the growth and the development of bone. Protein diet is an important factor, which will determine the optimal calcification during bone growth and development stages. Bone calcification, in orthodontics, can be used to estimate the bone maturity for diagnosis and treatment planning. The purpose of this study was to recognize ones ability to surpass calcium and phosphor deficiency because of pre and postnatal protein deficiency. There were three groups of samples of Rattus norvegicus rats. The first group was the control group with standard diet, the second was the infant group with pre and postnatal protein deficiency, and the third group was young rat at weaning age with pre and postnatal protein deficiency supplemented with enough protein in the diet. Bone calcification stage was analyzed: 1) Histologically by measuring epiphyseal width on right femur; 2) by measuring calcium and phosphor concentration on left femur with Spectrophotometry Atomic Absorption and spectroscopy ultra light visible. The data were analyzed by one way ANOVA continued by t test. The result showed that: 1) there was significant (p < 0.01) epiphyseal width difference between group I and II, I and III (p < 0,01) but there was not significant difference between group II & III (p > 0.05); 2) there was significant calcium and phosphor concentration on bone between group I, II and III (p < 0.01). It was concluded that bone calcification damage because of pre and post natal protein deficiency was an irreversible process. Protein supplement after bone calcification could not restore the condition.